Improved genetic markers for monitoring recruitment dynamics in the endangered Mary River cod (Maccullochella mariensis). (15th February 2018) - Schmidt, D. J.; Espinoza, T.; Real, K.; Dunlop, A.; Kennard, M.; Hughes, J. M.
Summary: The Mary River cod ( Maccullochella mariensis ) is a large predatory freshwater fish identified as a potential flagship for freshwater ecosystem conservation in Australia. The species is endemic to the Mary River catchment in eastern Australia, and is listed as Endangered. Previous conservation genetic assessment of Mary River cod was based on a small set of microsatellite loci developed for congeneric Maccullochella species. Here we develop a novel set of 15 microsatellite loci specific to M. mariensis, and demonstrate that these markers exhibit higher variability than those used previously. Mean number of alleles per locus was 4 and mean expected heterozygosity was 0.57. We genotyped 35 Mary River cod larvae belonging to a single cohort using the 15 novel loci and eight previously used loci, and found 10 full‐sib family groups along with clear genetic differentiation between individuals collected from the two sub‐catchments – Tinana Creek and Mary River. Microsatellites presented here will be useful for cost‐effective monitoring of genetic diversity and recruitment dynamics in this endangered fish species.